The 'Dark Side' of carbon peak pressure---based on real earning management of Chinese heavily polluting firms - Chu, Yichun; Abdul Rahim, Norhuda; Soh, Wei Ni; Haji Yahya, Mohamed Hisham (Spinger Nature, 2025)
COP 28 highlights the challenges associated with achieving a timely global consensus on carbon reduction measures within the framework of the Paris Agreement. As the deadline for promises nears, the increased pressure on China, a principal supporter of carbon emissions reductions, has raised fears about possible negative repercussions. This study investigates the impact of regional peak carbon pressures on firms' real earnings management by using a multiple linear regression approach with the sample of heavy polluters listed on China's A-share from 2015 to 2021. The findings suggest that higher regional peak carbon pressures lead to greater earnings management behaviour in heavy polluting enterprises as they face larger operational limits and higher costs for environmental investment and green transitions. These issues limit financial flexibility and total factor productivity, motivating earnings manipulation, which is more pronounced in non-state-owned enterprises and those with fewer environmental responsibilities. These findings highlight the unintended consequences of carbon policies on corporate behavior, exposing the requirement for governments to reassess environmental regulations to balance corporate sustainability with environmental protection goals